THE EFFECT OF WORD FIND GAME ON VOCABULARY MASTERY BY SEVENTH GRADE STUDENTS OF SMP DARUSSALAM MEDAN - Jamilah Susanti; Nova Andriani (Universitas Potensi Utama, 2021)
This purpose due to this study was to find the provement of word find game on Vocabulary Mastery . The method that was used quantitative method. The design of this study was experimental study. This study was conducted in SMP Darussalam Medan. The number of the sample of the studywas 60 students of seventhgrade. The instrument of this study was several tests. The tests were divided into two, there were pre-test and post-test. The data that were obtained from the tests were analyzed by using SPSS statisic 25 program. The result of the study showed that the mean score of post test in control class was 79.33 while the mean score of post-test in experimental was 84.00. Based on the criteria of hypothesis test that if sig. 2 tailed (p) was lower than alpha (α) 0.05, then Ho (Null Hypothesis) was rejected and Ha (Alternative Hypothesis) was accepted. In this study, the result of sig. 2 tailed was 0.003 and it proved that p <α. It showed that there was a significant to the word find game of students’ vocabulary mastery.